Exploring the Teaching of Reading in Lower Primary Classes: A Case Study of One Government Primary School in Kocheka Sub County, Uganda - Mrutu, Nipael; Kulwenza, Rachael (African Journal of Education and Practice, 2024)
Purpose: The purpose of this study was to investigates the methods teachers use to teach reading in lower primary classes at a government primary school in Kocheka Sub County, Uganda, focusing particularly on how these methods impact learners' reading competences. Methodology: A qualitative case study approach was utilized, employing interviews and document analysis to gather data from six teachers, one head teacher, and one District Inspector of Schools (DIS). Findings: The findings highlight the use of phonics, whole language, and balanced methods. Further, they reveal that teachers are conversant with these methods and understand how they affect learners’ reading skills. The DIS noted that his office provides textbooks for students and offers supervisory support via school inspectors. The data also indicated that the head teacher, in his management role, provides informal mentorship to lower primary teachers. Despite teachers’ familiarity with teaching methods and the support from the DIS and head teacher, challenges such as limited resources and large class sizes hindered their full effectiveness. Unique Contribution to Theory, Practice and Policy: The study recommends strengthening in-service and pre-service teacher training to equip educators with approaches to teaching reading in challenging, under-resourced contexts.